Pengaruh Jumlah Kunjungan Wisatawan, Pajak Hotel Restoran dan Pendapatan Asli Daerah terhadap Belanja Modal Kabupaten/Kota di Provinsi Bali - Widiana, I Nyoman Wahyu; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 11, November 2015 (pp.1328-1444), 2015)
Capital expenditure is the expenditure of local governments in building fixed assets at public service and then can maximize the productivity of the economy. This study to investigate the effect of direct and indirect number of tourist, tax of hotel and restaurant, and local revenues through capital expenditure. This research was conducted in all districts / cities in Bali. Data collection is through the documents contained in the BPS Bali Province, Bali Government Local Revenue Office and Bali Government Tourism Office. This study used secondary data with path analysis path analysis to determine the direct effect as sobel test to determine the effect is not immediate. The analysis showed that the number of tourist, tax of hotel and restaurant significant direct effect on the local revenues. Number of tourist, tax of hotel and restaurant and local revenue significant direct effect on the capital expenditure. Number of tourist and tax of hotel through local revenues significant indirect effect on the capital expenditure. Local revenue mean spending an intervening variable of number of tourist and tax of hotel and restaurant.
Keywords: KeywNumber of tourist; Tax of hotel and restaurant; Local revenue; Capital expenditure